2016
DOI: 10.1097/cad.0000000000000325
|View full text |Cite
|
Sign up to set email alerts
|

Subdural hematoma in a patient taking imatinib for GIST

Abstract: Although anticancer drugs have existed for over 50 years, targeted drugs have only recently been marketed, and their side effects may not be completely understood. The patient is a 56-year-old woman with a gastrointestinal stromal tumor who presented with headache, nausea, and vomiting lasting 2 weeks. An MRI to rule out brain metastasis found a large right-hemispheric subdural hematoma without metastases. She denied trauma, seizures, or alcohol abuse. Laboratory test results were normal. Eight months prior, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Both patients developed liver hematomas within four months of Imatinib initiation [ 9 ]. In other studies, subdural hemorrhages have been tied to Imatinib use [ 4 ]. A total of 1.9-5.7% of intracranial hemorrhages occur with concurrent imatinib use in the absence of alternative causes [ 4 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both patients developed liver hematomas within four months of Imatinib initiation [ 9 ]. In other studies, subdural hemorrhages have been tied to Imatinib use [ 4 ]. A total of 1.9-5.7% of intracranial hemorrhages occur with concurrent imatinib use in the absence of alternative causes [ 4 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, spontaneous non-traumatic mediastinal hematomas are rare [ 1 , 2 ]. There have been reports of Imatinib therapy for gastrointestinal stromal tumors (GIST) linked with hepatic and subdural hematomas [ 3 , 4 ]. Imatinib is a tyrosine kinase inhibitor that has been shown to arrest or even reverse the progression of GIST [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, they showed CNS disorders such as dizziness, headache, and paraesthesia associated with imatinib therapy in 14 patients, and hematological side effects such as anemia and leukopenia in 13 patients [7]. Theodotou et al reported a case of spontaneous subdural hematoma associated with platelet dysfunction in a patient with GIST who was on imatinib therapy [8]. GIS hemorrhage was reported two weeks after imatinib therapy in a patient with duodenal GIST in whom hemorrhage could be controlled by surgical intervention [9].…”
Section: Discussionmentioning
confidence: 99%